TO BUY OR NOT TO BUY: LANGUAGE AS A TOOL OF PERSUASION ON SOCIAL MEDIA - Asta Pukienė; Ugnė Lisauskaitė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Modern means of digital communication and the abundance of offered goods and services demand the implementation of new techniques for attracting consumers and swaying their purchasing behaviour. The current article aims to identify and describe the most common linguistic means and tools of persuasion used by influencers on social media. The paper suggests theoretical background of the language of social media in general, as well as the phenomenon of influencers and their impact on brand awareness and purchasing decisions. The practical analysis is based on the video footages of Jeffree Star, who is one of the most famous influencers in the digital environment with more than 20 million dedicated followers. The descriptive linguistic method was applied for processing the collected examples and revealing the most common linguistic techniques of persuasion that were used by the famous influencer while promoting his beauty products online. The analysis showed that ubiquitous social media has become an inseparable part of contemporary human life and interaction. Nowadays brand recognition, awareness and choices mostly depend on the influencers, who try to create a favourable content and establish a sense of bond and trust with their audience. In order to achieve that they employ a number of persuasion techniques ranging from the extensive use of emotive words to the instances of inclusive language. The collected examples, their analysis and the findings drawn at the end of the research are extremely relevant to a contemporary consumer who might get lost with a huge variety of products and goods available on the market. Being aware of the linguistic techniques that are used for the purpose of influencing and manipulating one’s purchasing behaviour a consumer might be able to identify true sincerity from the marketing gimmick.